Merit-based recruitment in the South African Public Service: Challenges and opportunities - Simon Matome Nkgapele; Sifiso Mofokeng (International Review of Social Sciences Research)
Section 195 (i) of South Africa’s Constitution mandates that public administration must reflect the nation's diversity, with recruitment and personnel management practices based on competence, fairness, and impartiality, while addressing historical inequalities to ensure broad representation. This creates a dual obligation for public administration: to foster inclusivity and equity while ensuring merit-based recruitment. Merit-based recruitment is crucial for meeting the public service's human resource needs and achieving employment equity by making opportunities accessible to all societal groups. While the practical application of merit-based recruitment presents opportunities, it still encounters considerable obstacles, such as political interference, and fragile institutional structures. This paper explored both the challenges and opportunities of merit-based recruitment in the South African public service through an analysis of government reports, academic literature, and policy reviews. The findings reveal that while the concept of merit-based recruitment is embedded in policy, its execution is hampered by political interference, nepotism, a lack of institutional capacity, skills shortages, and tensions between affirmative action and meritocracy. The paper recommends strengthening monitoring and evaluation measures employed by the Public Service Commission (PSC) to effectively promote and oversee the implementation of merit-based recruitment processes in the public service.